A tributação do consumo no Brasil e seus efeitos: análise e proposta de mitigação dos efeitos da regressividade inerente a esta modalidade de tributação - Monteiro Júnior, Nelson (2016)
This paper discusses the challenges of minimizing the taxation of consumption in Brazil, starting with an overview of the various taxable economic basis with emphasis on consumption, comparing it within their similarities, with developed and developing countries, with the influence of constitutional principles of proportionality and selectivity. Attempts to employ greater progressivity to the tax system will be analyzed as long as international models with applicability to the theme. Therefore, we will bring to light historical issues related to ICMS, their tax characteristics and the fruitless attempts of national tax reform and the failure of the proposals forward to the mitigation of regressive taxation. At the end, we present model proposed to combat these setbacks tax on consumption with relevant discussion the mechanisms necessary for their implementation.